Assessing the circularity status of waste management among manufacturing, waste management, and recycling companies in Kigali, Rwanda - Mulindwa, Mike Ssempa; Akor, Jackson; Auta, Mary; Nijman-Ross, Elke; Ogutu, Moses Onyango (Frontiers in Sustainability, 2024)
A high quantity of waste is generated from industrial activities by manufacturers across metropolitan cities compared to smaller cities with fewer industrial activities. Adopting Circular Economy principles in waste management has the potential for sustainable waste management to reduce the quantity of waste at dumpsites and harmful emissions from wastes. The study was conducted to assess circularity status and challenges for attaining higher circularity by Kigali’s manufacturing, waste collection and waste recycling companies using the 10-R framework. The study also sought to build estimates for industrial solid waste quantity and methane emissions for the next ten years (2020-2030) in Rwanda. A mixed method approach was utilized where primary data was collected from manufacturing, waste collection and waste recycling companies using a validated questionnaire and an in-depth interview guide. Thematic, descriptive analysis and First Order Decay methods were used to analyze the qualitative, quantitative and secondary data. Results show that adopting the 10-R principles of circular economy was low and varies across manufacturing, waste collection and recycling companies. There were instances of high adoption of R3-Reuse and R8-Recycle with a mean score of 7.17 and 7.21 among manufacturing companies. R7-Repurpose (8.80) recorded a high adoption rate among waste collection companies and a medium level of adoption for R7-Repurpose (3.50) and R9-Recover (3.00) among recycling companies. The overall low adoption towards attaining circularity was attributed to various economic, institutional, infrastructural, operational, attitudinal, and technological challenges. In 2030, it is projected that 922 Gigagram) of industrial waste will be deposited in solid waste disposal sites in Rwanda; with an estimated methane emission of 157 Gigagram Carbon dioxide equivalence. It was recommended among others, that human resource capacity development should be prioritized to drive the adoption of the 10-R principles across manufacturing, waste collection and waste recycling companies in Kigali, which can reduce the quantity of wastes that ends at dumpsites and methane emissions that contribute significantly to global warming.